A Study of Social Anxiety among Students - Misra, K.S. (JOURNAL OF INDIAN EDUCATION, 2020)
The present study attempts to compare social anxiety among male and female students studying in ninth, eleventh, B.A. Part I and III, and M.A. third semester grades. Social Anxiety Inventory constructed by K.S. Misra has been used to collect data. Data analysis has been done by using one-way analysis of variance and LSD tests through SPSS 22nd version. It has been found that male students of M.A. third semester exhibit more social anxiety than students of ninth and B.A. Part I students of Class XI exhibit more social anxiety than students of Class IX. This has been reported with reference to social anxiety related to prestige, performance, emotional well-being and separation too. Female students of Class IX exhibit more social anxiety than students of other grades; female students of M.A. third semester exhibit more social anxiety than students of B.A. Part I and III, and female students of Class XI exhibit more social anxiety than students of B.A. Part I and III.